Bridging the schism of schizophrenia through yoga—Review of putative mechanisms. (3rd May 2016) - Mehta, Urvakhsh Meherwan; Keshavan, Matcheri S.; Gangadhar, Bangalore N.
Abstract: Schizophrenia patients experience a 'disconnect' at multiple levels—neuronal networks, mental processes, and interpersonal relationships. The resultant poor quality-of-life and functional disability are related to the persistent cognitive deficits and negative symptoms, which are rather resistant to conventional antipsychotic medications. Yoga has emerged as an important therapeutic intervention to improve quality-of-life in schizophrenia. Recent preliminary evidence suggests that effects of yoga on cognitive and negative symptoms may drive this benefit. This study attempts to integrate evidence from neuroscience-based research, which focuses on the neuroplasticity-harnessing effects of yoga to bridge the schizophrenia connectopathy. In an overarching model to study putative neurobiological mechanisms that drive therapeutic effects of yoga, it is proposed that (a) various styles of meditation may help in strengthening the lateral and medial prefrontal brain networks, thus improving neurocognition and mentalizing abilities, and (b) learning and performing co-ordinated physical postures with a teacher facilitates imitation and the process of being imitated, which can improve social cognition and empathy through reinforcement of the premotor and parietal mirror neuron system. Oxytocin may play a role in mediating these processes, leading to better social connectedness and social outcomes. Clinical and heuristic implications of this model are further discussed.